Трехэлектродный воздушный коммутатор с графитовыми электродами КВТГ-50 на напряжение до ±50 кВ и импульсный ток амплитудой до ±220 кА - Баранов, М.И.; Рудаков, С.В.; Цехмистро, В.Л. (Електротехніка і електромеханіка, 2015)
Представлены основные технические характеристики и краткое описание конструкции высоковольтного трехэлектродного сильноточного воздушного коммутатора с графитовыми электродами КВТГ-50 на номинальное напряжение ±50 кВ. Созданный образец коммутатора предназначен для работы в разрядной цепи мощного высоковольтного
генератора нормированных микросекундных импульсов тока искусственной молнии с амплитудой Im=±(200±20) кА
при их длительности τp=(350±35) мкс на уровне 0,5·Im. Данный коммутатор каскадного типа из-за применения графитовых электродов обладает повышенным рабочим ресурсом и повышенной стабильностью срабатывания при его
использовании в составе генератора тока имитированной линейной молнии. Представлені основні технічні характеристики і короткий опис конструкції високовольтного трьохелектродного сильнострумового повітряного комутатора з графітовими електродами КВТГ-50 на номінальну напругу ±50 кВ. Створений
зразок комутатора призначений для роботи в розрядному колі потужного високовольтного генератора нормованих мікросекундних імпульсів струму штучної блискавки з амплітудою Im=±(200±20) кА при їх тривалості τp=(350±35) мкс на
рівні 0,5·Im. Даний комутатор каскадного типу із-за застосування графітових електродів володіє підвищеним робочим
ресурсом і підвищеною стабільністю спрацьовування при його використанні у складі генератора струму імітованої
лінійної блискавки. Purpose. Development and creation of the simplified construction of a high-voltage heavy-current air three-electrode
switchboard with graphite electrodes, intended for operation in
composition the powerful generator of large impulsive current
of artificial of linear lightning. Methodology. Electrophysics
bases of technique of high-voltage and scientific and technical
bases of planning of devices of high-voltage impulsive technique. Results. Developed and made a new construction of a
high-voltage heavy-current air three-electrode switchboard with
the graphite electrodes of KATG-50 on nominal voltage ±50 kV.
This construction of switchboard KATG-50 has been passed
experimental approbation in composition the heavy-current bit
chain of powerful high-voltage generator of the аperiodic impulses of current of artificial linear lightning rationed on operating foreign standards with amplitude of Im=±(200±20) кА at
their duration τP=(350±35) μs at level 0,5·Im. Originality. First
in domestic practice of development and creation of highvoltage heavy-current switchboards for the generators of large
impulse currents of artificial lightning the ground of necessity of
the use for their basic and managing electrodes of electrical
engineering graphite is carried out. Practical value. The developed and made high-voltage heavy-current switchboard of cascade-tray KATG-50 from application in its composition of
graphite electrodes possesses an enhanceable working resource
and enhanceable stability of wearing-out at the use of similar
switchboard in the bit chain of powerful pulsed current of the
imitated linear lightning.